SEA-ICE TRANSPORT OF RIVERINE PARTICLES FROM THE LAPTEV SEA TO FRAM STRAIT BASED ON CLAY MINERAL STUDIES - Dethleff D.; Rachold V.; Tintelnot M.; Antonow M. (My University, 2000)
The aim of this study was to identify pathways and processes of modern sediment transport from the Siberian hinterland to the Laptev Sea and further to the Arctic Ocean. Clay mineral analyses were performed on riverine suspended particulate material (SPM), surface sediments of the Laptev Sea shelf, and sea-ice sediments (SIS). Material collected during seven expeditions was included in this study. Clay mineral assemblages are used to decipher the distribution of riverine sediments on the shallow Laptev Sea shelf, the entrainment of fine particles into newly forming ice, and the transport of SIS from the Laptev Sea towards the ablation areas. A cluster analysis of our data set shows that the clay mineral assemblages of Laptev Sea shelf sediments and SIS are controlled mainly by the input of riverine SPM supplied by the Khatanga, Lena, and Yana Rivers. Whereas the western shelf clay-mineral province is characterized by enhanced smectite concentrations supplied by the Khatanga River, the eastern Laptev Sea is dominated by illite discharged through the Lena and Yana Rivers. The SIS smectite concentration serves as an indicator for sediment source areas on the circum-Arctic shelves. Subsequently, the Transpolar Drift can be distinguished into a Siberian Branch fed from the eastern Kara Sea and the western Laptev Sea, and a Polar Branch originating from the eastern Laptev Sea.